2017
DOI: 10.1007/s00210-017-1388-x
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsive activity of (1S)-(−)-verbenone involving RNA expression of BDNF, COX-2, and c-fos

Abstract: (1S)-(-)-verbenone (VRB) is a monoterpene present in the essential oils of many plants which has shown therapeutic effect; however, its anticonvulsant activity has not yet been evaluated. The present work sought to investigate the anticonvulsant activity of VRB using pilocarpine and pentylenetetrazole-induced seizure testing; seeking also probable mechanisms of action. VRB caused no significant changes in motor coordination. Also, no significant data was observed in the pilocarpine-induced seizure tests. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…It is worth mentioning that the antioxidant activity reported for flavonoid metabolites is relevant since processes of epileptogenesis and oxidative damage have been observed and since these processes can contribute to the initiation and progression of epileptic seizures [35,36]. Terpenoids have also been shown to exhibit neuroprotective properties [37], and some have anticonvulsant effects [38]. Some reports have shown that sesquiterpenoids modulate GABA A receptors [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the antioxidant activity reported for flavonoid metabolites is relevant since processes of epileptogenesis and oxidative damage have been observed and since these processes can contribute to the initiation and progression of epileptic seizures [35,36]. Terpenoids have also been shown to exhibit neuroprotective properties [37], and some have anticonvulsant effects [38]. Some reports have shown that sesquiterpenoids modulate GABA A receptors [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…at 10 mg/kg (n = 5/dose group) to male SD rats (8 weeks old; (255-275) g; Koatech Inc., Gyeonggi, Republic of Korea) housed individually in metabolic cages. Urine samples were collected for ((0-4), (4)(5)(6)(7)(8) and (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)) h. Pooled urine samples were mixed with equal volume of acetonitrile containing HSDH (1 µg/mL) as IS, followed by filtration with a syringeless filter device (Mini-UniPrep™, PTFE filter media with polypropylene housing, 0.45 µm). The filtrate was analyzed by Agilent 6530 Q-TOF LC-MS/MS system equipped with dual AJS ESI ion source and Agilent 1200 series HPLC system, as follows.…”
Section: In Vivo Metabolite Identificationmentioning
confidence: 99%
“…Verbenone-containing essential oils have been reported to have various biological activities that include antibacterial activity against oral pathogens, antinociceptive activity in formalin-induced licking actions in mice, anti-inflammatory activity in carrageenan-induced pleurisy in mice and antiulcer effect in acute ethanol-induced gastric lesions in rats [1,3]. One of the enantiomers (1S)-(−)-verbenone showed excellent acaricidal activity against house dust mites and elicited an anticonvulsive effect in pentylenentetrazol-induced seizures in mice by regulating RNA expression of the neurotrophin brain-derived neurotrophic factor, the transient proto-oncogene protein c-fos and cyclooxygenase 2 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Carvacryl acetate increases GABA neurotransmitter levels in the hippo-campus [181]. Another important mechanism of EOs compounds is the reduction of seizure-induced inflammation and/or oxidative stress as observed in α-asarone, (-)-verbenone, β-caryophyllene, borneol, carvacryl acetate, eugenol and nerolidol [117,136,158,181,208,235,282]. Some constituents of EOs such as eugenol, terpinen-4-ol and thymol are able to reduce seizures via the modulation of ion channels [206,256,272].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Verbenone derivatives present important biological characteristics such as antifungal [279], antiviral [280], antioxidant activities and (in cortical neurons) anti-ischemic properties [281]. Given these promising effects, Melo et al [282] evaluated the anticonvulsant activity of verbenone at doses of 150, 200, and 250 mg/kg (i.p.). Initially, they found that verbenone was unable to alter motor coordination in the animals and had no effect in pilocarpine-induced seizure test, as it did not alter latency to seizures or reduce peripheral cholinergic signals.…”
Section: (-)-Verbenonementioning
confidence: 99%